The Role of Artificial Intelligence in Enhancing Customer Experience: A Case Study of Global E-commerce Platforms - Sulastri, Lilis (GoAcademica Research & Publishing, 2023)
This study explores the pivotal role of Artificial Intelligence (AI) in enhancing customer experience on global e-commerce platforms. Through an extensive literature review, we examine how AI-driven technologies, such as personalized recommendations, chatbots, and predictive analytics, are transforming customer interactions and satisfaction. The findings suggest that AI not only streamlines operations but also provides significant value by tailoring experiences to individual customer preferences. Moreover, the study highlights the challenges and ethical considerations in implementing AI, particularly in maintaining data privacy and transparency. The implications of AI adoption in e-commerce are profound, influencing both consumer behavior and business strategies globally. This paper contributes to the ongoing discourse on digital transformation, offering insights for practitioners and researchers alike. Ultimately, the study underscores the importance of balancing technological innovation with ethical responsibility to achieve sustainable growth in the e-commerce sector.